Pengaruh Pengetahuan Keuangan, Sikap Keuangan dan Kepribadian terhadap Perilaku Manajemen Keuangan UMKM di Desa Kesilir - Ramadhanni Youwana (Jurnal Manajemen, Bisnis dan Kewirausahaan, 2026)
An important role is played by Micro, Small, and Medium Enterprises (MSMEs) in the economy, but many MSME entrepreneurs face limitations in financial literacy and financial management. This study aims to analyze wheter or not an effect that received by the financial management behavior of MSMEs in Kesilir Village from financial knowledge, financial attitudes, and personality. This quantitative study with an associative causal approach used a sample of 140 respondents representing the population of local MSME entrepreneurs. The questionnaires are used to collect data research and multiple linear regression is implemented to analyze that data with the help of SPSS version 27. The results indicate that financial management behavior is positively and significantly effected by financial knowledge and personality, while financial attitudes have a negative and significant influence. These findings confirm that improving financial literacy and strengthening individual character can encourage better financial management, but certain financial attitudes can hinder the effectiveness of financial management. In conclusion, financial education interventions accompanied by personality development are needed to improve the financial management capacity of MSMEs so that they can survive and thrive in competition.